1996
DOI: 10.1016/s0006-3495(96)79602-9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the viscoelastic properties of human platelets with the atomic force microscope

Abstract: We have measured force curves as a function of the lateral position on top of human platelets with the atomic force microscope. These force curves show the indentation of the cell as the tip loads the sample. By analyzing these force curves we were able to determine the elastic modulus of the platelet with a lateral resolution of approximately 100 nm. The elastic moduli were in a range of 1-50 kPa measured in the frequency range of 1-50 Hz. Loading forces could be controlled with a resolution of 80 pN and inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
548
3
10

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 777 publications
(586 citation statements)
references
References 42 publications
25
548
3
10
Order By: Relevance
“…This research confirmed that the hydrodynamic drag force exhibits a locally pure viscous behavior and that the drag factor is dependent upon distance between the tip and the substrate. The authors pointed out that previous attempts to correct AFM measurements for hydrodynamic drag effects consisted of estimating the drag force at some distance above the specimen and then using this value to correct the measurements taken on contact [21][22][23]. However, it is expected that this approach will lead to an underestimation of the actual hydrodynamic drag at contact and the authors noted that applying corrective drag force measurements taken at even a few microns above the sample can lead to significant errors in the measured forces.…”
Section: Introductionmentioning
confidence: 99%
“…This research confirmed that the hydrodynamic drag force exhibits a locally pure viscous behavior and that the drag factor is dependent upon distance between the tip and the substrate. The authors pointed out that previous attempts to correct AFM measurements for hydrodynamic drag effects consisted of estimating the drag force at some distance above the specimen and then using this value to correct the measurements taken on contact [21][22][23]. However, it is expected that this approach will lead to an underestimation of the actual hydrodynamic drag at contact and the authors noted that applying corrective drag force measurements taken at even a few microns above the sample can lead to significant errors in the measured forces.…”
Section: Introductionmentioning
confidence: 99%
“…SPM can also be used to evaluate mechanical properties, because its probe is in physical contact with the samples during measurement. To obtain cellular stiffness with SPM, two methods have been proposed, namely, a force modulation mode [22,23] and a force mapping mode [24]. According to experiments performed by using these methods, the local stiffness of fibroblasts is not homogeneous on the cellular surface, but varies largely from point to point [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In 1996, Radmacher et al [74] applied AFM in the force-mapping mode to monitor the mechanical properties of human platelets. The pseudonucleus, which comprises the cytosol and small vesicles, was found to be the softest part of these bodies (Young's modulus, 1.5-4 kPa), whereas the outer filamentous zone, which consists of bundles of actin filaments and microtubules, was up to tenfold stiffer (Young's modulus, 10-40 kPa).…”
Section: Eukaryotesmentioning
confidence: 99%